Effect of face-to-face psychoeducation intervention combined with motivational interviewing on adherence in prevention and treatment of pulmonary tuberculosis patients - Choliq, Idham; Nasrullah, Dede; Sukadiono, Sukadiono; Fitriyani, Vika Ramadhana (University of Muhammadiyah Malang, 2023)
Introduction: TB can be cured if patients routinely seek treatment for six months without breaking. Poor adherence to tuberculosis treatment is a global health challenge. Whereas adherence to the treatment regimen is important for tuberculosis (TB) control. The consequences of this non-compliance lead to treatment failure and the risk of infection of the disease is widespread. Objectives: The objective of the study is to examine what Face-to-Face Psychoeducation Intervention Combined with Motivational Interviewing effective to improve Adherence in Prevention and Treatment of Pulmonary Tuberculosis Patients. Methods: The research design used quantitative with experimental quasi research design t. The research was conducted at 4 Community Health Centers (Puskesmas), namely Puskesmas Takal, Puskesmas Perak, Puskesmas Pegirian and Puskesmas Sutopo in Surabaya. Through purposive sampling, the sample number was 60 respondents, divided by 30 respondents for the intervention group and 30 respondents for the control group. Results: There was a significant difference after the intervention. In the intervention group, there were changes in outcomes in both preventive adherence (12.37) and medication adherence (4.52). While in the control group, only the value of prevention compliance experienced a change of 5.67. Conclusions: Face-to-face method combined with motivation interviewing is effective in improving prevention and treatment adherence in TB patients. Motivational interviewing has a tendency to reduce hopelessness, an increasing motivation to recover and the admonition of taking medication in tuberculosis patients.